PENDAFTARAN PATEN PENGETAHUAN TRADISIONAL DALAM PERSPEKTIF KEPASTIAN HUKUM - Manurung, Susi Marlinda; Sumanto, Listyowati (Ensiklopedia Education Review, 2024)
Abstract: Traditional knowledge is knowledge owned by the hereditary community. In its development, there is traditional knowledge that is used as the origin of a patent invention so in Article 26 of Law No. 13/2016 concerning Patents, it is required that patent applications originating from traditional knowledge must state the origin of the traditional knowledge as determined by an official institution recognized by the government. Currently, the management of traditional knowledge is carried out by 3 (three) institutions, namely the Ministry of Education and Culture, the Ministry of Law and Human Rights, and the Ministry of Environment and Forestry. Still, from the activities of these institutions, none have been officially recognized by the government to issue a determination of traditional knowledge that is the origin of a patent registration application. The system in mentioning the origin of conventional knowledge in patent registration applications needs to be studied through 3 aspects: structure, substance, and legal culture.Keywords: Traditional Knowledge, Patent, System.